Analisis Sistem Pengendalian Internal Terhadap Persediaan dengan menggunakan Kerangka Kerja COSO pada CV. Rona Karya Nusantara - Jolissetiawati, Handayani; Nurmalina, Rina; Dahtiah, Neneng; Muhammad, Rahma Nazila (Indonesian Accounting Literacy Journal, 2025)
Inventory must be managed properly to avoid risks that are detrimental to the company. An effective internal control system is able to assist companies in securing their assets. Based on the preliminary study, it was found that every year the company always experiences a difference in inventory. Therefore the purpose of this study is to analyze the internal control over the applied inventory. The analytical method used is descriptive qualitative with a case study approach, the research data sources use primary and secondary data obtained through interviews, observation and documentation. The analysis carried out will follow the internal control guidelines proposed by COSO. The results of the research show that the internal control system implemented by the company has not been effective in dealing with risks in inventory management activities. This is indicated by the incomplete components and principles of internal control implemented by the company.